Acquisition of Mycobacterium abscessus among ventilator-dependent patients in Taiwan chronic respiratory care facilities. (April 2016) - Lee, Meng-Rui; Tsai, Chia-Jung; Hu, Jia-Ying; Lee, Shih-Wei; Ko, Jen-Chung; Wang, Hao-Chien; Yu, Chong-Jen; Lee, Li-Na; Hsueh, Po-Ren
Aim: To investigate the acquisition of Mycobacterium abscessus among ventilator-dependent patients.Materials & methods: We prospectively recruited ventilator-dependent patients in five respiratory care wards (RCWs). Respiratory specimens were cultured for mycobacteria on day 1 (D1), 3 months (M3) and 6 months (M6) after enrollment.Results: 72 patients had cultures taken at all three time points. The proportion of patients with a culture positive for M. abscessus increased from 15.3% (11/72) on D1 to 30.6% (22/72) at M3 and 38.9% (28/72) at M6. Two M. abscessus subspecies abscessus isolates obtained from different patients had identical randomly amplified polymorphic DNA patterns. Being in RCW D and advanced age were significantly associated with initial cultures positivity.Conclusion: Our study reveals that acquisition of M. abscessus was common among ventilator-dependent patients.